The Effect of Performance Management System on Lecturer Excellence and Satisfaction in Private Universities in Bogor City - Efrita Norman; Heni Feviasari; Faiz Aizat (MES Management Journal, 2025)
This research investigates the impact of performance management systems on the excellence and satisfaction of lecturers at private higher education institutions in Bogor. The background of the study highlights the critical role that higher education institutions play in developing human resources and contributing to societal progress, especially amidst global competition and rapid technological advancement. Lecturers, as the core element of education, significantly influence the achievement of the institution's goals, which makes performance management essential. The purpose of this research is to analyze how the implementation of performance management systems influences the professional excellence and satisfaction of lecturers. The research utilizes a quantitative approach with a descriptive analytical design, collecting data from 192 lecturers across four private universities in Bogor using surveys and documentation methods. The study shows that performance management systems, particularly through goal setting, performance evaluation, and professional development, have a significant positive effect on both lecturer excellence and job satisfaction. Results indicate that clear performance targets, transparent evaluations, and constructive feedback are crucial factors influencing lecturer performance and satisfaction. The study contributes to the field by providing empirical evidence on the importance of effective performance management systems for improving institutional competitiveness, enhancing lecturer motivation, and supporting continuous professional development. The research also suggests practical recommendations for higher education administrators to optimize performance management systems, contributing to the institution’s long-term success.